La competencia por los derechos antárticos: Chile y Argentina en la zona austral (1890–1910 - Manzano Itura, Karen Isabel (2018)
During the last decades of the 19th century, the discoveries in the southernmost area of the planet showed the existence of a sixth continent, Antarctica, by which the closest countries competed for their sovereignty. At the beginning of the 20th Century, Chile and Argentina confronted each other for this dilemma, since both countries quarreled for the recently discovered lands, and thus, increasing their geopolitical projection to the South for both of them. In this article, we analyze the main facts of this dispute occurred from 1890 to 1910, when the abovementioned States established their first formal claims. For that purpose a qualitative methodology will be used, based on review of sources that were produced in a space bounded time that starts at the end of the 19th century to the beginning of the 20th century. Durante as últimas décadas do século XIX, descobertas na parte sul do planeta demonstraram a existência de um sexto continente, a Antártida, pelo qual os países mais próximos disputavam sua soberania. No início do século XX, o Chile e a Argentina enfrentavam-se nesse dilema, pois ambos disputavam as novas terras descobertas, aumentando sua projeção geopolítica para o sul. Este artigo analisará essa disputa entre 1890 e 1910, quando esses Estados estabeleceram suas reivindicações formais por meio de uma metodologia qualitativa baseada na revisão de fontes produzidas em um espaço de tempo limitado, entre o final do século XIX e o início do século XX. Durante las últimas décadas del siglo XIX, los descubrimientos en la zona austral del planeta demostraron la existencia de un sexto continente, la Antártida, por el cual los países más cercanos se disputaron su soberanía. A inicios del siglo XX, Chile y Argentina se encontraban frente a frente en este dilema, ya que ambos se disputaban las nuevas tierras descubiertas, aumentando su proyección geopolítica al sur. El presente artículo analizará esta disputa entre 1890 hasta 1910, cuando aquellos Estados establecieron sus reclamaciones formales mediante ...